METHODOLOGY OF SYSTEM APPROACHE TO SEISMIC RISK ASSESSMENT AND REDUCTION - A. D. Abakarov; I. B. Kurbanov (Вестник Дагестанского государственного технического университета: Технические науки, 2016)
Abstract. Ensuring of urban areas seismic safety is a task which do not require delay. But it cannot be solved by separate parts. It is essential that all components of the seismic hazard must be grouped together in one problem based on the system approach. In the present paper is presented not only the main flowchart of systems approach to ensuring the territory seismic safety but also the flowcharts of components of each main unit. They cover the whole package of measures for a full assessment of territory seismic hazard, seismic risk and its reduction.The proposed methodology can be carried out for design and implementation of regional territory seismic safety programs.